Nitric oxide prevents H(2)O(2)-induced apoptosis in SK-N-MC human neuroblastoma cells - Yoo, Yeong-Min (Int J Biol Sci, 2018)
Nitric oxide (NO) is a cellular signaling molecule in many physiological and pathological processes including neuroprotector. Here we examined the antiapoptotic effect of NO in SK-N-MC cells. H(2)O(2) treatment (10-200 μM) induced cell death in a dose-dependent manner and pretreatment of cells with 100 μM S-nitroso-N-acetylpenicillamine (SNAP), an NO donor, attenuated the occurrence of H(2)O(2)-induced cell death. DAPI staining showed H(2)O(2)-induced nuclear fragmentation and NO treatment suppressed it. NO inhibited the proteolytic activation of caspase-3 and mitochondrial cytochrome c release. Treatment of soluble guanylyl cyclase inhibitor ODQ decreased the protective effect of SNAP on H(2)O(2)-treated cells and increased caspase 3-like enzyme activity and activation, cytochrome c release, PARP cleavage, and DNA fragmentation, indicating that cGMP is a key mediator in NO-mediated antiapoptosis. The cGMP analog 8-Br-cGMP blocked H(2)O(2)-induced apoptotic cell death; reduction of caspase-3 enzyme, cytochrome c release, and caspase-8 and -9. These preventive effects of SNAP and 8-Br-cGMP were suppressed by PKG inhibitor KT5823. Levels of PKGI, PKGII, and p-VASP proteins were increased by SNAP and 8-Br-cGMP and suppressed by KT5823 treatment. These results indicate that PKG is a downstream signal mediator in the suppression of apoptosis by NO and cGMP. Akt activation was inhibited the PI3K inhibitors LY294002 and Wortmannin, resulting in the inhibition of cell viability and increase of cytochrome c release. SNAP induced phosphorylation of Akt and Bad and then increased the interactions between 14-3-3β and p-Bad. These data suggest that the NO suppresses H(2)O(2)-induced SK-N-MC cell apoptosis by suppressing apoptosis signal mediating the interaction between 14‐3‐3β and Bad phosphorylation via PKG/PI3K/Akt.